Preparation method and application of mayenite-based composite material electrode
The electrode preparation by composited with calciumite and bismuth oxide or graphite solves the problem of difficulty in effectively detecting the concentration of chloride ion in water in the prior art, and achieves a fast, accurate and economical chloride ion detection effect.
Patent Information
- Application Number
- CN202211359949.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-02
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-11-02
AI Technical Summary
It is difficult for the prior art to effectively detect the concentration of chloride ion in water, especially when the chloride ion content exceeds the standard, which causes huge harm to biological survival, industrial production and ecological sustainability.
By composited with bismuth oxide or graphite, a casmuthium/bismuth oxide composite electrode and a casmuthium/graphite composite electrode were prepared and applied to the detection of chloride ions in a water environment.
This method significantly improves the enrichment performance of the electrode surface to chloride ions, can quickly and accurately detect chloride ion concentration, and has the advantages of economical, easy to operate and high sensitivity.
Smart Images

Figure CN115852414B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a preparation method and application of a mayenite-based composite material electrode. Background Art
[0002] Chloride ions are everywhere in the environment. Different forms of chlorine exist in soil, water, and air. Almost all water on Earth contains chlorine, mostly in the form of magnesium and sodium salts. These natural chloride ions have a great harm to the health of organisms. - It can also be used with water containing Na + , Ca 2+ Mg 2+ , K + Phosphate ions of various metal salts such as chlorine and chlorine interact with each other to form polymetallic chlorides, which directly causes the groundwater of most lakes on the earth to naturally form sedimentary strata containing chloride salt deposits, causing serious impacts on the water environment. Not only in the natural environment, but also in industrial production and building structures, chloride ions are easily polarized and accelerate the corrosion of products and industrial equipment, which also has a huge impact on industry. - The sources are mainly human life and industrial sewage and the development of new energy and new technology. These industries include soap industry, alkali industry, leather industry and fur processing industry, pickled food industry, etc. When the chloride concentration in water is too high, it will seriously corrode underground metal pipeline facilities, buildings and other engineering structures on the ground, hinder the healthy growth of soil plant roots, affect the chemical decomposition and activity of copper zinc in neutral acidic soil, cause excessive salinization of groundwater and soil, and endanger the life and health of organisms. Therefore, when the chloride ion content exceeds the standard, it will cause great harm to biological survival, industrial production and ecological sustainability. Human standards for chloride ion detection are getting higher and higher, so accurate measurement of chloride ion concentration is an urgent issue to be solved.
[0003] Currently, the widely used quantitative detection methods for chloride ion concentration in water include volumetric method, potentiometric titration, electrochemical analysis, mercury titration, silver chloride visual turbidimetry, capillary electrophoresis and ion chromatography, as well as some newly developed detection technologies such as flow injection, paper-based microfluidics and flow injection analysis combined methods. - Detection methods have different applications, fields and detection accuracy, and each of these methods has its own advantages and disadvantages. Among these processing methods and technologies, electrochemical analysis technology has the advantages of simple determination method, rapid analysis, high sensitivity and cheap large-scale analytical instruments. It can be measured by converting chemical parameters and chemical quantities that are difficult to directly measure and interpret into simple and easy-to-measure electrochemical parameters, and at the same time, the electrical signal is quickly converted and transmitted to the computer for quantitative analysis, and the experimental data can be obtained in an instant.
[0004] Caalenite has obvious advantages in electrochemical stability and flexible preparation in various sample forms (including single crystal, thin film, polycrystalline block and powder). Bi2O3 has 1 / 4 oxygen ion positions in its lattice that are vacant, so it has very high oxygen ion conductivity and can be used to make various solid oxide fuel cells and oxygen sensors.
[0005] How to combine mayenite with other materials to obtain composite electrodes and apply them to Cl - The detection of is the technical problem to be solved by the present invention. Summary of the invention
[0006] In order to solve the above technical problems, a preparation method and application of a mayenite-based composite material electrode are provided. The method of the present invention obtains a mayenite / bismuth oxide composite material electrode and a mayenite / graphite composite material electrode, which are applied to detect chloride ions in a water environment and have good responsiveness to chloride ions.
[0007] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0008] A method for preparing a mayenite-based composite material electrode comprises the following steps:
[0009] (1) grinding an inorganic material selected from bismuth oxide and graphite and mayenite in a mass ratio of 1-5:1, then adding an aqueous solution of chitosan, stirring evenly, and drying to obtain a mayenite-based composite modified material;
[0010] (2) mixing the mayenite-based composite modified material with water to form a suspension, coating the suspension on a clean glassy carbon electrode surface, and obtaining a mayenite-based composite material electrode after drying;
[0011] The mayenite-based composite material electrode is specifically a mayenite / bismuth oxide composite material electrode or a mayenite / graphite composite material electrode.
[0012] Furthermore, the amount of chitosan in the chitosan aqueous solution is 10-20% of the total mass of the inorganic material and the mayenite.
[0013] Furthermore, the mayenite is obtained by uniformly mixing calcium oxide and aluminum oxide in a molar ratio of 1-1.3:1 and then calcining at 1200-2000° C. for 0.5-2h.
[0014] Furthermore, the concentration of the mayenite-based composite modified material in the suspension is 0.013-0.015 g / mL.
[0015] Furthermore, the coating amount of the suspension on the surface of the glassy carbon electrode is 5-7 μL.
[0016] On the other hand, the present invention provides a mayenite-based composite material electrode obtained by the above-mentioned preparation method for use in the detection of chloride ions in an aqueous environment. The application method is: placing the mayenite-based composite material electrode as a voltammetric sensor in an electrolytic cell of a three-electrode system, the bottom liquid is a PBS buffer solution containing chloride ions, the pH is adjusted to 5-8, the enrichment potential of the cyclic voltammetric scan is set to -0.3V to -0.1V, and the enrichment time is 50s to 200s, and the chloride ion concentration in the bottom liquid is detected by cyclic voltammetric scanning and differential pulse voltammetry.
[0017] Preferably, the pH is adjusted to 6; the enrichment potential is -0.2 V, and the enrichment time is 100 s.
[0018] Beneficial technical effects:
[0019] The present invention compounds calcium aluminum with graphite or bismuth oxide, and the obtained composite material is used as a modification material for the electrode to modify the electrode to obtain a calcium aluminum / graphite composite material electrode and a calcium aluminum / bismuth oxide composite material electrode, which are used to determine the anion Cl - , which can greatly increase the electrode surface to anion Cl - The calcium aluminate / graphite composite material electrode has excellent conductivity and can promote the adsorption of chloride ions by calcium aluminate, and the calcium aluminate / graphite composite material has a good response to chloride ions. In the calcium aluminate / bismuth oxide composite material electrode, since both calcium aluminate and bismuth oxide have good adsorption effects on chloride ions, under electrochemical action, chloride ions can be fixed in the lattice of calcium aluminate and bismuth oxide, thereby showing good chloride ion response characteristics. The calcium aluminate-based composite material electrode prepared by the present invention is used to determine chloride ions and has the advantages of being economical and practical, easy to operate, having little secondary pollution, and having high sensitivity, and can effectively, accurately, and quickly detect chloride ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the DPV diagram of the mayenite / graphite composite electrode of Example 2 used for detecting chloride ions.
[0021] Figure 2 This is the DPV diagram of the calcium aluminum oxide / bismuth oxide composite electrode of Example 1 used for detecting chloride ions.
[0022] Figure 3 XRD pattern of the calcium aluminum oxide / graphite composite electrode of Example 2.
[0023] Figure 4 XRD pattern of the calcium aluminum oxide / bismuth oxide composite electrode of Example 1. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.
[0025] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0026] The experimental methods in the following examples without specifying specific conditions are usually measured according to national standards; if there is no corresponding national standard, it is carried out according to the general international standards or the standard requirements proposed by relevant enterprises. Unless otherwise specified, all parts are by weight and all percentages are by weight.
[0027] The processing method of the clean glassy carbon electrode involved in the following embodiments is: before polishing, gently wipe the surface of the glassy carbon electrode with a moistened lens paper to remove dirt and ensure that the surface of the electrode is smooth; rub the glassy carbon electrode back and forth in an "8" shape on velvet paper (there must be aluminum oxide powder on the velvet, and water is sprayed on it), after polishing for 10 minutes, change to another particle size of aluminum oxide powder (in order of 1μm, 0.3μm, 0.05μm) and repeat the above steps. After each polishing, rinse the glassy carbon surface with distilled water, then wash with pure water, nitric acid, and ethanol in turn, and then ultrasonically clean with ultrapure water and anhydrous ethanol; then activate: connect the polished electrode to the electrochemical workstation with three electrodes; configure potassium ferrocyanide PBS solution for voltammetric scanning (to ensure that the potential difference is within 100mV), and obtain a clean glassy carbon electrode that has been polished, polished, and activated by cyclic voltammetric scanning 20 times in the range of -0.8 to +0.8V.
[0028] The bismuth oxide used in the following examples is commercial bismuth oxide or is prepared by precipitation with bismuth nitrate and sodium hydroxide.
[0029] The preparation method of mayenite used in the following examples is as follows: calcium oxide and aluminum oxide are uniformly mixed in a molar ratio of 1.2:1 and then calcined at 2000° C. for 1 hour to obtain the mayenite.
[0030] Example 1
[0031] A method for preparing a calcium aluminum oxide / bismuth oxide composite material electrode comprises the following steps:
[0032] (1) grinding bismuth oxide and mayenite in a mass ratio of 1:1 and then adding an aqueous solution of chitosan (the amount of chitosan added is 20% of the total mass of bismuth oxide and mayenite), using chitosan as a binder to highly compound bismuth oxide and mayenite, and then drying to obtain a mayenite / bismuth oxide composite modified material;
[0033] (2) The dried calcium aluminum oxide / bismuth oxide composite modified material is mixed with water to prepare a suspension with a concentration of 0.015 g / mL, and 6 μL of the suspension is coated on the surface of a clean glassy carbon electrode. After drying, a calcium aluminum oxide / bismuth oxide composite material electrode is obtained.
[0034] The XRD pattern of the product in this example is as follows Figure 4 As shown by Figure 4 It can be seen that the material contains Bi2O3 and Ca 12 Al 14 O 33 , and the X-ray diffraction intensity of both is very high, indicating that the Bi2O3 and Ca 12 Al 14 O 33 The content is very high.
[0035] Example 2
[0036] A method for preparing a calcium aluminum / graphite composite electrode comprises the following steps:
[0037] (1) Graphite and mayenite are ground evenly in a mass ratio of 1:1, and then an aqueous solution of chitosan is added (the amount of chitosan added is 10% of the total mass of bismuth oxide and mayenite), chitosan is used as a binder to highly compound bismuth oxide and mayenite, and then dried to obtain a mayenite / graphite composite modified material;
[0038] (2) The dried calcium aluminum oxide / graphite composite modified material is mixed with water to prepare a suspension with a concentration of 0.015 g / mL, and 6 μL of the suspension is coated on the surface of a clean glassy carbon electrode. After drying, a calcium aluminum oxide / graphite composite material electrode is obtained.
[0039] The XRD pattern of the product in this example is as follows Figure 3 As shown by Figure 3 It can be seen that the material contains C and Ca 12 Al 14 O 33 , and the X-ray diffraction intensity of both is very high, indicating that the carbon and Ca in the sample 12 Al 14 O 33 The content is very high.
[0040] Example 3
[0041] The calcium aluminum / bismuth oxide composite electrode of Example 1 and the calcium aluminum / graphite composite electrode of Example 2 were respectively placed in an electrolytic cell of a three-electrode system as voltammetric sensors, and the bottom liquid was PBS standard solution + 1 mol / L NaCl solution (the volume ratio of the two was 2:1), and the pH was adjusted to 6. After adding voltage on the CHI660 electrochemical workstation, the chloride ion concentration in the bottom liquid was detected by differential pulse voltammetry at an enrichment potential of -0.2 V and an enrichment time of 100 s. The results are shown in FIG. Figure 1 and Figure 2 shown.
[0042] Figure 1 is a DPV diagram of the calcium aluminum oxide / graphite composite electrode of Example 2 for detecting chloride ions, Figure 1 It can be seen that the calcium aluminum stone / graphite composite material electrode has an obvious response to this concentration of chloride ions and has good sensitivity. The minimum concentration of chloride ions that can be detected is 0.1 mol / L.
[0043] Figure 2 is a DPV diagram of the calcium aluminum stone / bismuth oxide composite material electrode of Example 1 for detecting chloride ions, Figure 2 It can be seen that the calcium aluminum stone / bismuth oxide composite material electrode has an obvious response to this concentration of chloride ions and has good sensitivity. The minimum concentration of chloride ions that can be detected is 0.1 mol / L.
[0044] Compare Figure 1 and Figure 2 It can be seen that the calcium aluminum ore / bismuth oxide composite electrode has a better response effect to chloride ions than the calcium aluminum ore / graphite composite electrode, and its sensitivity is relatively high. This may be because both calcium aluminum ore and bismuth oxide have good adsorption characteristics for chloride ions. Chloride ions can enter the lattice of calcium aluminum ore and bismuth oxide and be fixed, while chloride ions are only adsorbed on the surface of graphite. Therefore, the DPV curve of the calcium aluminum ore / graphite composite electrode is relatively unstable.
[0045] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a mayenite-based composite material electrode, characterized in that: The steps include: (1) grinding an inorganic material selected from bismuth oxide and graphite and mayenite in a mass ratio of 1-5:1, then adding an aqueous solution of chitosan, stirring evenly, and drying to obtain a mayenite-based composite modified material; The mayenite is obtained by mixing calcium oxide and aluminum oxide in a molar ratio of 1-1.3:1 and then calcining at 1200-2000°C for 0.5-2h; (2) mixing the mayenite-based composite modified material with water to form a suspension, coating the suspension on a clean glassy carbon electrode surface, and obtaining a mayenite-based composite material electrode after drying; The mayenite-based composite material electrode is specifically a mayenite / bismuth oxide composite material electrode or a mayenite / graphite composite material electrode.
2. The method for preparing the mayenite-based composite material electrode according to claim 1, characterized in that: The amount of chitosan in the chitosan aqueous solution is 10-20% of the total mass of the inorganic material and the mayenite.
3. The method for preparing the mayenite-based composite material electrode according to claim 1, characterized in that: The concentration of the mayenite-based composite modified material in the suspension is 0.012-0.015 g / mL.
4. The method for preparing the mayenite-based composite material electrode according to claim 1, characterized in that: The coating amount of the suspension on the surface of the glassy carbon electrode is 5-7 μL.
5. Application of the mayenite-based composite material electrode obtained by the preparation method according to any one of claims 1 to 4 in detecting chloride ions in a water environment, characterized in that: The application method is: placing the calcium aluminum oxide-based composite material electrode as a voltammetric sensor in an electrolytic cell of a three-electrode system, the bottom liquid is a PBS buffer solution containing chloride ions, the pH is adjusted to 5-8, the enrichment potential of the cyclic voltammetric scan is set to -0.3V to -0.1V, and the enrichment time is 50s to 200s, and the chloride ion concentration in the bottom liquid is detected by cyclic voltammetric scanning and differential pulse voltammetry.
6. The use according to claim 5, characterized in that: The pH was adjusted to 6; the enrichment potential was -0.2 V, and the enrichment time was 100 s.
Citation Information
Patent Citations
Method of manufacturing conductive mayenite type compound
JP2006327894A
Electrode for use in synthesis by electrolytic reduction, and method for synthesizing organic compound by electrolytic reduction
JP2010261086A